Formation and development of the educator’s digital competence in a lifelong learning system as a demand of modern times - Kharkivska А. (Problems of Engineer-Pedagogical Education, 2020)
The article analyzes the phenomenon of digitalization which rapidly covers almost all spheres of adult activity. It’s about the digital economy, digitalization of manufacturing, financial sector, businesses and professions. Education is at the epicenter of digitalization. The most important transformation is currently underway, which is the transition from offline to online environments or digitizing. Global digitalization has a significant impact on increasing the demand for teaching staff. An educator who does not possess modern digital skills and cannot use them in his or her professional activity is unlikely to be able to ensure the quality of the educational process. This actualizes the problem of increasing digital competence of the educator in accordance with the tasks of modernization of education. The research deals with the problem of formation and development of digital competence, which is one of the key competences of educators. The essence of the concept «competence» and different approaches to defining digital competence of educators are analyzed. Scientific methods of analysis, synthesis, observation, description and comparison have been used to determine the peculiarities of the formation and development of educators’ digital competence in lifelong learning. The findings confirm that digital competence can be interpreted as a willingness and ability to navigate the digital space, to use digital technologies to access, search, process, evaluate, produce, use, and disseminate information in one’s own professional activity. In the process of formation and development of this competence, the educator should acquire knowledge and skills in the field of application of digital technologies; develop digitalbased communication skills; be able to navigate the professional digital environment; receive and analyze new information; carry out self-analysis and reflect on professional activities. The author also defines the principles of formation and development of digital competence of educators. An analysis of the European Commission project «Digital Competence of Educators (DigCompEdu)» has been conducted, the content of which defines the directions for enhancing the digital competence of pedagogical staff in the lifelong learning system.